JWST MIRI and NIRCam observations of NGC 891 and its circumgalactic medium - Chastenet, Jérémy; Looze, Ilse De; Relaño, Monica; Dale, Daniel A.; Williams, Thomas G.; Bianchi, Simone; Xilouris, Emmanuel M.; Baes, Maarten; Bolatto, Alberto D.; Boyer, Martha L.; Casasola, Viviana; Clark, Christopher J. R.; et al. (Astronomy and astrophysics, 2024)
We present new JWST observations of the nearby, prototypical edge-on, spiral galaxy NGC 891. The northern half of the disk was observed with NIRCam in its F150W and F277W filters. Absorption is clearly visible in the mid-plane of the F150W image, along with vertical dusty plumes that closely resemble the ones seen in the optical. A ∼10 × 3 kpc2 area of the lower circumgalactic medium (CGM) was mapped with MIRI F770W at 12 pc scales. Thanks to the sensitivity and resolution of JWST, we detect dust emission out to ∼4 kpc from the disk, in the form of filaments, arcs, and super-bubbles. Some of these filaments can be traced back to regions with recent star formation activity, suggesting that feedback-driven galactic winds play an important role in regulating baryonic cycling. The presence of dust at these altitudes raises questions about the transport mechanisms at play and suggests that small dust grains are able to survive for several tens of million years after having been ejected by galactic winds in the disk-halo interface. We lay out several scenarios that could explain this emission: dust grains may be shielded in the outer layers of cool dense clouds expelled from the galaxy disk, and/or the emission comes from the mixing layers around these cool clumps where material from the hot gas is able to cool down and mix with these cool cloudlets. This first set of data and upcoming spectroscopy will be very helpful to understand the survival of dust grains in energetic environments, and their contribution to recycling baryonic material in the mid-plane of galaxies.
Gesehen am 19.08.2025